Eksplorasi Etnomatematika pada Arsitektur Masjid Besar Gondanglegi Sebagai Sumber Belajar Geometri - Anggita Oktaviana Putri (CONSISTAN (Jurnal Tadris Matematika), 2024)
This study aims to explore the ethnomathematical elements embedded in the architecture of the Grand Mosque of Gondanglegi and its potential as a learning resource for geometry in schools. A qualitative approach with ethnographic methods was employed, collecting data through observation, interviews, and documentation. The research seeks to describe the geometric concepts present in the mosque's architectural cultural elements and how they can be linked to culturally-based mathematics education.The findings reveal that the architecture of the Grand Mosque of Gondanglegi incorporates various geometric shapes such as triangles, rectangles, circles, and rhombuses, evident in elements like domes, minarets, and windows. These elements not only hold aesthetic value but also reflect a blend of Javanese, Madurese, and Middle Eastern cultures. The mosque's architecture serves as a tangible example of applying geometric concepts in real life, which can motivate and enhance students’ understanding in mathematics learning.This study contributes to the development of contextual, culture-based learning by emphasizing the importance of integrating local cultural elements into mathematics teaching. Furthermore, the findings are expected to help preserve Islamic cultural values through education while offering innovative strategies for teachers to create meaningful and engaging learning experiences for students.